Plant defense approach of Bacillus subtilis (BERA 71) against Macrophomina phaseolina (Tassi) Goid in mung bean. Issue 1 (1st January 2017) - Hashem, Abeer; Abd_Allah, Elsayed Fathi; Alqarawi, Abdulaziz A.; Radhakrishnan, Ramalingam; Kumar, Ashwani
ABSTRACT: This study was aimed to elucidate the mitigation mechanism of an endophytic bacterium, Bacillus subtilis (BERA 71) against Macrophomina phaseolina (Tassi) Goid disease in mung bean. M. phaseolina reduced the plant growth by inducing disease, hydrogen peroxide (H2 O2 ) and lipid peroxidation . The inoculation of B. subtilis to diseased plants increased chlorophyll, ascorbic acids, and superoxide dismutase, catalase, peroxidase, ascorbate peroxidase and glutathione reductase activities, and while inhibited H2 O2 and lipid peroxidation for enhancing plant growth. In addition, B. subtilis association in plants mitigated the M. phaseolina infection due to increase of indole acetic acids and indole butyric acid, and also a decrease of abscisic acid. However, the nutrients (N, K, Ca, Mg, Zn, Cu, Mn and Fe) were increased, except Na in M. phaseolina diseased plants treated with B. subtilis . The result of this study suggests that B. subtilis interaction with plants can modulate the metabolism of pigments, hormones, antioxidants and nutrients against M. phaseolina to induce disease resistance in mung bean.